21 Temporal trends in survival of patients with and without diabetes following out-of-hospital cardiac arrest: a nationwide danish study. (16th April 2018) - Mohr, Grimur Høgnason; Søndergaard, Kathrine Bach; Pallisgaard, Jannik Langtved; Møller, Sidsel Gamborg; Wissenberg, Mads; Karlsson, Lena; Møller Hansen, Steen; Kragholm, Kristian; Køber, Lars; Lippert, Freddy; Folke, Fredrik; Vilsbøll, Tina; et al.
Abstract : Aim: In Denmark, survival from out-of-hospital cardiac arrest (OHCA) has increased markedly following national initiatives to improve cardiopulmonary resuscitation (CPR). 1, 2, 3 However, whether the temporal improvement in OHCA survival also applied for diabetics is unknown. Method: Patients>18 years with OHCA of presumed cardiac cause were identified from the Danish Cardiac Arrest Registry during 2001–2014. Patients with prescriptions for glucose-lowering drugs up to 180 days before OHCA were identified as diabetics. Associations between diabetes and return of spontaneous circulation (ROSC) upon hospital arrival and 30 day survival were estimated with logistic regression adjusted for patient- and OHCA-related characteristics. In total, 28, 955 OHCA cases were included and 4276 (14.8%) of those were diabetics. Compared to non-diabetics, diabetics had higher prevalence of comorbidity, same prevalence of bystander witnessed arrests (42.0% vs 43.2%) and bystander CPR (51.7% vs 52.7%), more arrests in residential locations (77.3% vs 73.0%) and were less likely to have initial shockable heart rhythm (23.5% vs 27.9%). From 2001 to 2014, temporal increases of ROSC (from 8.8% to 22.3% among diabetics vs 7.8% to 25.7% among non-diabetics) and 30 day survival (from 2.8% to 9.7% among diabetics vs 3.5% to 14.8% among non-diabetics) were observed in both patient groups (P for trends<0.001). Diabetes was associated with decreased probability of achieving ROSC (odds ratio (OR) 0.75 [95% confidence interval (CI) 0.67 to 0.84]) as well as 30 day survival (OR 0.57 [95% CI: 0.47 to 0.68]). Results: ROSC and 30 day survival increased in patients with and without diabetes. However, diabetes was associated with lower odds of ROSC and 30 day survival. References: . Hansen SM, Hansen CM, Folke F, et al. Bystander defibrillation for out-of-hospital cardiac arrest in public vs residential locations. JAMA Cardiol 2017;2(5):507–514. doi:10.1001/jamacardio.2017.0008 . Wissenberg M, Lippert FK, Folke F, et al. Association of national initiatives to improve cardiac arrest management with rates of bystander intervention and patient survival after out-of-hospital cardiac arrest. Jama2013;310:1377–1384. doi:10.1001/jama.2013.278483 . Hansen SM, Wissenberg M, Rajan S, et al. Rapport fra dansk hjertestopregister 2001 – 2014 . http://genoplivning.dk/wp-content/uploads/2016/05/Rapport-fra-Dansk-Hjertestopregister-2001-2014.pdf [Accessed: 7 June 2017]. Conflict of interest: None Funding: None